Anionic Lipid Catalyzes the Generation of Cytotoxic Insulin Oligomers - Jhinuk Saha; Audrey Wolszczak; Navneet Kaur; Malitha C. Dickwella Widanage; Samuel D. McCalpin; Riqiang Fu; Jamel Ali; Ayyalusamy Ramamoorthy (Biomolecules, 2025)
The misfolding and aggregation of proteins into amyloidogenic assemblies are key features of several metabolic and neurodegenerative diseases. Human insulin has long been known to form amyloid fibrils under various conditions, which affects its bioavailability and function. Clinically, insulin aggregation at recurrent injection sites poses a challenge for diabetic patients who rely on insulin therapy. Furthermore, decreased responsiveness to insulin in type 2 diabetic (T2D) patients may lead to its overproduction and accumulation as aggregates. Earlier reports have reported that various factors such as pH, temperature, agitation, and the presence of lipids or other proteins influence insulin aggregation. Our present study aims to elucidate the effects of non–micellar anionic DMPG (1,2–dimyristoyl–sn–glycero–3–phosphoglycerol) lipids on insulin aggregation. Distinct pathways of insulin aggregation and intermediate formation were observed in the presence of DMPG using a ThT fluorescence assay. The formation of soluble intermediates alongside large insulin fibrils was observed in insulin incubated with DMPG via TEM, DLS, and NMR as opposed to insulin aggregates generated without lipids. 13C magic angle spinning solid–state NMR and FTIR experiments indicated that lipids do not alter the conformation of insulin fibrils but do alter the time scale of motion of aromatic and aliphatic side chains. Furthermore, the soluble intermediates were found to be more cytotoxic than fibrils generated with or without lipids. Overall, our study elucidates the importance of anionic lipids in dictating the pathways and intermediates associated with insulin aggregation. These findings could be useful in determining various approaches to avoid toxicity and enhance the effectiveness of insulin in therapeutic applications.